2011
DOI: 10.1016/j.bbrc.2011.06.111
|View full text |Cite
|
Sign up to set email alerts
|

A new function of Nell-1 protein in repressing adipogenic differentiation

Abstract: A theoretical inverse relationship has long been postulated for osteogenic and adipogenic differentiation (bone versus adipose tissue differentiation). This inverse relationship in theory at least partially underlies the clinical entity of osteoporosis, in which marrow mesenchymal stem cells (MSCs) have a predilection for adipose differentiation that increases with age. In the present study, we assayed the potential anti-adipogenic effects of Nell-1 protein (an osteoinductive molecule). Using 3T3-L1 (a human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 36 publications
1
70
1
Order By: Relevance
“…1E). Consistent with published reports in other cell types, 28,32 hPSCs treated with NELL-1 protein (300 ng/mL) showed an increase in both ALP and AR staining at 5 and 10 days of osteogenic differentiation, respectively (Fig. 1D, E).…”
Section: Isolation and In Vitro Differentiation Of Hpscsupporting
confidence: 81%
See 2 more Smart Citations
“…1E). Consistent with published reports in other cell types, 28,32 hPSCs treated with NELL-1 protein (300 ng/mL) showed an increase in both ALP and AR staining at 5 and 10 days of osteogenic differentiation, respectively (Fig. 1D, E).…”
Section: Isolation and In Vitro Differentiation Of Hpscsupporting
confidence: 81%
“…19,28,* In the current study we directly compared the effect so BMP-2 and NELL-1 in PSC-mediated ectopic bone formation. Significantly, different qualities in bone regenerate were found: while BMP-2 induced a higher density of bone, this was also intermixed with lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Because canonical Wnt inhibitors did not completely eliminate the antiadipogenic effect of NELL-1 on BMP2-induced adipogenesis, we hypothesize that other pathways, such as Hedgehog signaling, may be involved in adipogenic regulation. 81 The ability of NELL-1 to activate Wnt signaling suggests potential utility in conditions such as osteoporosis, in which the balance between osteogenesis versus adipogenesis and the balance between bone deposition versus resorption are perturbed to favor bone loss.…”
Section: Potential Applications For Nell-1 In the Clinicmentioning
confidence: 89%
“…NELL-1 has been reported to induce robust osseous healing of critical-sized rat femoral segmental and calvarial defects [17,25,26], and also to promote lumbar spinal fusion in rats, sheep [21][22][23], and non-human primates. Additionally, NELL-1 has been identified not only to demonstrate anti-osteoclastic effects both in vitro and in vivo [19], but also to suppress adipogenesis [27]. Recently, a genomewide linkage study identified NELL-1 polymorphisms in patients with reduced bone mineral density [28], thus describing an association between NELL-1 and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%